Coupled dynamics investigation of a tunnel immersion system under beam and oblique waves. (1st December 2020) - Song, Yue; Sun, Zhenxiang; Huang, Guoxing; Chen, Nianzhong
Abstract: A 3D experimental investigation is conducted to simultaneously measure the motions of tunnel and pontoon of a tunnel immersion system under the action of beam and oblique regular waves. The importance of wave incident direction on coupled dynamics of the system (tunnel motion, pontoon motion, relative motion, suspension tensions and mooring tensions) is discussed in terms of various wave periods and immersion depths. It is concluded that the sensitivity of the system dynamics to the wave incident direction is strongly dependent on wave period and immersion depth. The wave heading angle plays a more important role in smaller immersion depth and when the wave period is close to certain natural periods or in relatively long wave regime. For the small immersion depth, the oblique wave excitations compared to the beam waves can incur higher tensile forces in the suspension lines and the mooring lines of the tunnel.